Propuesta de diseño para la certificación sommelier en la escuela de Gestión en Empresas Turísticas y Hoteleras GESTURH de la Pontificia Universidad Católica del Ecuador Sede Ibarra PUCE-SI - Flores Maldonado, Crhistopher Israel (2021)
The objective of this research was to develop an academic proposal for the sommelier certification at the GESTURH School of the Pontificia Universidad Católica del Ecuador - Ibarra Headquarters in order to diversify the current academic offer. In order to achieve this, the following research question was determined: How does the design of a sommelier certification influence the current academic diversification of the Pontificia Universidad Católica del Ecuador Sede Ibarra? The methodology used for the aforementioned work begins with a basic investigation and a mixed approach, the same one that developed three types of investigation: bibliographic, descriptive and exploratory\; 60 people were surveyed, including gastronomy students and teachers from the Pontificia Universidad Católica del Ecuador Sede Ibarra and the Universidad Técnica del Norte\; Likewise, professionals from the technical and academic area were interviewed in order to obtain relevant information that helps in the development of the academic proposal. The aforementioned information was obtained between the month of November and December 2020. Among the results, it was found that the respondents encourage the development of the proposal since they relate it as an opportunity for personal and professional growth, the same that generates job competitiveness\; They believe it is necessary to promote a wine culture in Imbabura and Ecuador\; Matters related to wine must be offered in Ecuador since at the moment there is no gastronomic culture in the country\; A large part of those surveyed would choose to train as sommeliers at PUCE-SI due to the history and prestige that this institution has. The proposal must be designed in such a way that it has more of a practical than a theoretical part, currently it is possible to accept virtuality and therefore a distance or blended learning\; It is important to make strategic alliances with academic, technical or food and beverage entities in order to offer a quality certification.